Online impulsive and compulsive buying behavior in Vietnam - Luong, Ha Thu; Tran, Dung Manh; Pham, Hang Minh; Nguyen, Trang Thu; Duong, Hoa Thi (International Journal of Management and Sustainability, 2023)
This study aims to investigate the factors contributing to online impulsive and online compulsive buying behaviours among Vietnamese consumers, given the increasing prevalence of online shopping. A survey of 562 participants (104 offline and 548 online) and Partial least squares structural equation model (PLS-SEM) were recruited to empirically examine the proposed research model. We found that (1) Performance Expectancy, Facilitating Conditions, Social Influence, Effort Expectancy and Stimulus shared positive relations with Online Buying Intention; (2) Scarcity posed significant impact on both Online Impulsive and Compulsive Buying Behaviors; (3) Online Buying Intention was only a key determinant of Online Impulsive Buying Behavior; and (4) Online Impulsive Buying proved to be a significant predictor of Online Compulsive Buying Behavior. By integrating the Unified Theory of Acceptance and Use of Technology (UTAUT) model with Stimulus-Organism-Response (SOR) framework, the research revealed a meaningful underlying mechanism regarding how consumers’ technological acceptance, platforms’ stimulus, and scarcity can motivate their actual impulsive and compulsive purchasing behaviors in prevalent online settings. Platform designers should offer more and more technological usefulness and conveniences to increase consumers’ online buying intentions, while marketers should consider scarcity as the focal point of their strategies.